The Petrogenesis of the Permian Podong Ultramafic Intrusion in the Tarim Craton, Western China: Constraints from C-He-Ne-Ar Isotopes. (22nd August 2019) - Zhang, Mingjie; Feng, Pengyu; Li, Tong; Li, Liwu; Fu, Juerong; Wang, Peng; Wang, Yuekun; Li, Zhongping; Wang, Xiaodong
Abstract : The Podong Permian ultramafic intrusion is only one ultramafic intrusion with massif Ni-Cu sulfide mineralization in the Pobei layered mafic-ultramafic complex, western China. It is obviously different in sulfide mineralization from the nearby coeval Poyi ultramafic intrusion with the largest disseminated Ni-Cu sulfide mineralization and mantle plume contribution (Zhang et al., 2017). The type and addition mechanism of the confirmed crustal contaminations and possible mantle plume involved in the intrusion formation require evidences from carbon and noble gas isotopic compositions. In the present study, we have measured C, He, Ne, and Ar isotopic compositions of volatiles from magmatic minerals in the Podong ultramafic intrusion. The results show that olivine, pyroxene, and plagioclase minerals in the Podong intrusion have variable δ 13 C of CO2 (-24.5‰ to -3.2‰). The CH4, C2 H6, C3 H8, and C4 H10 hydrocarbon gases show normal or partial reversal distribution patterns of carbon isotope with carbon number and light δ 13 C1 value of CH4, indicating the hydrocarbon gases of biogenic origin. The δ 13 C of CO2 and CH4 suggested the magmatic volatile of the mantle mixed with the volatiles of thermogenic and crustal origins. Carbon and noble gas isotopes indicated that the Podong intrusion could have a different petrogenesis from the Poyi ultramafic intrusion. Two types of contaminated crustal materials can be identified as crustal fluids from subducted altered oceanic crust (AOC) in the lithospheric mantle source and a part of the siliceous crust. The carbon isotopes for different minerals show that magma spent some time crystallizing in a magma chamber during which assimilation of crustal material occurred. Subduction-devolatilization of altered oceanic crust could be the best mechanism that transported large proportion of ASF (air-saturated fluid) and crustal components into the mantle source. The mantle plume existing beneath the Poyi intrusion could provide less contribution of real materials of silicate and fluid components.